PENGARUH FAKTOR INTERNAL DAN FAKTOR EKSTERNAL TERHADAP MINAT BERWIRAUSAHA (STUDI KASUS PADA MAHASISWA FEBI IAIN LANGSA - fasya, fasya (Al - Muamalat, 2018)
This study aims to determine the magnitude of direct and indirect influence of internal factor variables in the form of entrepreneurship education and entrepreneurial motivation and external factors in the form of family environment to entrepreneurial interests. The study population is all FEBI IAIN Langsa students who have taken entrepreneurship courses. Samples were taken with nonprobability sampling technique of purposive sampling, and the number of samples were 60 active students. The research method used survey method with quantitative approach. Data analysis using path analysis with the help of MSI program, SPSS version 16 and LISREL 8.8 (student). Based on the results of research internal factors in the form of entrepreneurship education and entrepreneurship motivation and external factors in the form of family environment have a positive and significant impact on entrepreneurial interests.